Living Hadis as A Lifestyle (A portrait of the Dialectics of Hadis and Culture in Indonesia) - Faticha Sadiyah (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2020)
The intersection between religion and culture is one of the characteristics of Islam in Nusantara, especially in Indonesia, including a people understanding of the Hadis. In the fact, until now, the traditions of Indonesia is contain of qur’anic and hadis spirit. The result of this paper, the author considers that living sunnah is not only a learning or researching, but it has become a model of understanding of Indonesian people towards it or it’s become a lifestyle of moslem in Indonesia that is always make ‘hadis is live’ or ‘live on the sunnah.’The forms of living hadis can not be separated from the connection of hadis with the culture. This can be seen from the tradition in Indonesia such as praying for people who have died, mauludan, haul, halal bi halal, and berkatan. Some of these tradition are the character of Islam in Indonesia. As stated by dialectical theory, the hadis and the culture are two opposites thing. However, both of them can be reconciled. For example, the tradition of berkatan/ tumpengan, this tradition is an implementation of the advise of giving in Islam. So, the consequnce of the implementation of this understanding are different because it has connected with culture in Indonesia